Effects of miR-144 on the sensitivity of human anaplastic thyroid carcinoma cells to cisplatin by autophagy regulation. Issue 6 (3rd June 2018) - Liu, Jing; Feng, Liguo; Zhang, Haitao; Zhang, Jin; Zhang, Yanyan; Li, Shujing; Qin, Long; Yang, Ziyao; Xiong, Jianxia
ABSTRACT: Background : We investigated the influence of miR-144 on the cisplatin-sensitivity of anaplastic thyroid carcinoma (ATC) cells and explored the internal molecular mechanism of miR-144. Methods : Thyroid cancer cells ARO, TPC1 and normal thyroid cells HT-ori3 were used in this research. Expressions of miR-144 and TGF-α were uncovered by western blot and qRT-PCR. Expressions of autophagy-related protein LC3 II and apoptosis-related protein Caspase-3 and PARP were explored by western blot and immunofluorescence. Cell viability was detected by MTT assay and apoptosis condition was revealed by flow cytometric analysis and TUNEL staining. Dual-luciferase reporter assay was employed to verify the target relationship. Tissue sections were detected by IHC. Xenograft assay was conducted to further verify conclusions in vivo . Results : MiR-144, which was low expressed in ATC cells and tissues, could inhibit autophagy activation induced by cisplatin, enhancing the sensitivity of ATC cells to cisplatin, and promoting cell apoptosis. TGF-α was the target of miR-144 and was negatively regulated by it. MiR-144 could improve the sensitivity of ATC cells to cisplatin and inhibit tumor growth by suppressing TGF-α both in vitro and in vivo . Conclusion : MiR-144 could inhibit autophagy of ATC cells by down-regulating TGF-α, enhancing the cisplatin-sensitivity of ATC cells.